Charm City Rocks : a love story - Norman, Matthew, 1977- (Dell, 2023)
"When a single dad meets the former rock star crush of his youth, everything they thought they knew about happiness and love is thrown into chaos in this hopeful, heartwarming romantic comedy Billy Perkins is happy. No, for real. It's kind of his thing, actually. And why wouldn't he be? He loves his job as an independent music teacher and his apartment in Baltimore above a record shop called Charm City Rocks. Most of all, he loves his brainy teenage son, Caleb. Although not the world's most traditional parent, Billy has plenty to teach his son about art and manhood before Caleb goes off to college. Margot Hammer, on the other hand, is far from happy. The former drummer of the once-famous rock band Burnt Flowers, she's now a rock and roll recluse living alone in New York City. When a new music documentary suddenly puts Margot back in the spotlight, she begins to realize how much she misses her old band and the music that gave her life meaning. Billy has always had a crush on Margot. But she's a legitimate rock star-or at least, she was-so he never thought he'd actually meet her. Until Caleb, worried that his easygoing dad might actually be lonely, cooks up a scheme to get Margot to perform at Charm City Rocks. It's the longest of long shots, but Margot's label has made it clear that any publicity is an opportunity she can't afford to miss. When their paths collide, Billy realizes that he maybe wasn't as happy as he thought-and Margot learns that sometimes the sweetest music is a duet"--